Can leukotriene receptors inhibitors preserve cognitive functions in asthma patients? Leukotriene receptors inhibitors and cognition - Aleksic, Dejan; Lazarevic, Snezana; Susa, Romana; Lazic, Zorica; Cekerevac, Ivan; Toncev, Gordana (Medicinski časopis, 2025)
Background: Recent research suggests that neuroinflammation may play a crucial role in age-related cognitive dysfunction. Studies have investigated the impact of leukotriene receptor inhibitors (LTR) antagonist montelukast, a medication commonly used to treat allergies and asthma, on the risk of developing dementia. The aim of this study was to compare cognitive functions in asthmatic patients who used and who don’t use montelukast and healthy controls. Method: In this study 50 asthmatic patients (age 67.34±6.44) (20 montelukast users and 30 montelukast nonusers) were matched with 50 healthy controls (age 68.08±5.95). Each participant was assessed with the Mini Mental State Examination (MMSE) and the Montreal Cognitive Test (MoCA). Memory coefficients (verbal, visual, general, delayed memory, and attention and concentration) were measured by Wechsler Memory Scale-Revised (WMS-R). Results: Orientation as MoCA subdomain was worse in patients with asthma compared to the control group (p=0.048). Asthmatic patients treated with montelukast had a significantly higher MoCA score (p=0.033) (dominantly due to delayed recall) (p=0.044) than patients without montelukast treatment. People with asthma on montelukast therapy showed statistically significantly better results on the MoCA test (p=0.037) compared to the control group (dominantly due to attention (p=0.032) and delayed recall (p=0.021)). Conclusion: Montelukast group compared to montelukast nonusers had better results on MoCA (dominantly due to delayed recall). Studies with a larger number of participants are needed to confirm the effect of montelukast on the cognitive status of the elderly.